2018
DOI: 10.6118/jmm.2018.24.3.188
|View full text |Cite|
|
Sign up to set email alerts
|

The Roles of Menopausal-specific Quality of Life on Breast Cancer Screening Beliefs in Menopausal and Postmenopausal Women

Abstract: ObjectivesThis study investigated the association between menopausal-specific quality of life (MENQOL) and breast cancer screening beliefs among Hong Kong Chinese menopausal and postmenopausal women.MethodsA cross-sectional study was employed to collect data. The questionnaire was distributed to a convenience sample of 218 women aged above 45. The outcome variables were breast cancer screening beliefs and breast examination. Multiple regression analyses were conducted to test the effect of 4 domains in MENQOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The present study demonstrated that women who had benign breast tumors were more likely to have functional well-being QoL. In our study, women who had regular breast self-examinations had better QoL, the results were similar with study results of Cheng et al [24], which showed that the breast and Pap smear screening rate was higher for women with better QoL. Although the association between women receiving cancer screening and QoL is still unclear, research suggests that women who have higher QoL may have better self-efficacy, optimistic personality and greater likelihood of having healthy behavior [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated that women who had benign breast tumors were more likely to have functional well-being QoL. In our study, women who had regular breast self-examinations had better QoL, the results were similar with study results of Cheng et al [24], which showed that the breast and Pap smear screening rate was higher for women with better QoL. Although the association between women receiving cancer screening and QoL is still unclear, research suggests that women who have higher QoL may have better self-efficacy, optimistic personality and greater likelihood of having healthy behavior [25].…”
Section: Discussionsupporting
confidence: 92%
“…It's consistent with previous studies that women with high health literacy may be more motivated to engage in preventive health behaviors and tend to avoid risky habits. When women with better general health status were more likely to participate in health screening behavior and with better general QoL (psycho-social and physical domains) [24,30].…”
Section: Discussionmentioning
confidence: 99%